Divisions in Motion: Visual Affective Polarization on TikTok During the 2024 European Parliament Elections - Pérez-Díaz, Pedro Luis; Zamora-Medina, Rocío; Pérez-Escolar, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Visual polarization is a key element of digital political communication, reinforcing group identity and deepening affective divisions. During the 2024 European elections, radical and far-right candidates used TikTok to modernize their image and promote polarizing, anti-establishment narratives. An analysis of N = 190 videos posted by seven candidates reveals a preference for emotionally charged, simplified content while avoiding interactive features. This strategy fostered in-group cohesion, heightened ideological divides, and increased the risk of misinformation, limiting substantive debate and mobilization. These findings highlight the role of visual rhetoric in shaping contemporary political discourse and its impact on polarization in digital environments.